A Cautionary Note on the Use of Exchange Rate Indicators - Wickham, Peter (IMF Policy Discussion Papers; Policy Discussion Paper ;, 1993)
The paper reviews the basis for the use of various popular exchange rate indicators by tracing their conceptual development, the links between these indicators, and how they are measured in actual practice. It also considers the difficulties often encountered in attempting to obtain empirical counterparts to the various concepts and the limitations on the use of indicators likely to arise therefrom. The paper illustrates the behavior of various exchange rate indicators using data for Colombia and Kenya. This is a Paper on Policy Analysis and Assessment and the author(s) would welcome any comments on the present text. Citations should refer to a Paper on Policy Analysis and Assessment of the International Monetary Fund, mentioning the author(s) and the date of issuance. The views expressed are those of the author(s) and do not necessarily represent those of the Fund.